2008
DOI: 10.1007/s00418-008-0542-4
|View full text |Cite
|
Sign up to set email alerts
|

New morphological aspects of blood islands formation in the embryonic mouse hearts

Abstract: Vasculogenesis in embryonic hearts proceeds by formation of aggregates consisting of erythroblasts and endothelial cells. These aggregates are called blood-islands or blood-island-like structures. We aimed to characterize blood islands in mouse embryonic hearts at stages spanning from 11 dpc through 13 dpc, i.e. prior to the establishment of the coronary circulation. Our observations suggested that there are two types of blood islands. One formed by migrating nucleated erythroblasts, which associated with migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 58 publications
0
11
0
1
Order By: Relevance
“…A third wave of hematopoiesis in the heart occurs between E11 and E14, and involves the formation of cardiac blood islands from the ventricular endocardium (Ratajska et al, ; Red‐Horse et al, ; Jankowska‐Steifer et al, ). Cardiac blood islands balloon out from the ventricular endocardium near the interventricular sulci and are associated with Runx1 + hematopoietic cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A third wave of hematopoiesis in the heart occurs between E11 and E14, and involves the formation of cardiac blood islands from the ventricular endocardium (Ratajska et al, ; Red‐Horse et al, ; Jankowska‐Steifer et al, ). Cardiac blood islands balloon out from the ventricular endocardium near the interventricular sulci and are associated with Runx1 + hematopoietic cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Between E11 and E14 ventricular endocardial cells near the interventricular sulci balloon outwards into the myocardium (Jankowska-Steifer et al, 2015, Red-Horse et al, 2010, Ratajska et al, 2009, Ratajska et al, 2006). These protrusions, called cardiac blood islands consist primarily of erythroblasts and megakaryocytes circumscribed by a single layer of endocardial cells (Jankowska-Steifer et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…These protrusions, called cardiac blood islands consist primarily of erythroblasts and megakaryocytes circumscribed by a single layer of endocardial cells (Jankowska-Steifer et al, 2015). Cardiac blood islands are thought to pinch off from the ventricular endocardium and fuse with the coronary vessels, contributing to the development of the coronary vasculature (Ratajska et al, 2009, Red-Horse et al, 2010). We also noted the apparent merging of extravascular islands with the vasculature in the embryo proper.…”
Section: Resultsmentioning
confidence: 99%
“…Formation of so-called blood-islands containing erythroblasts and endothelial cells normally precedes vasculogenesis. Ratajska et al (2009) now characterized blood islands in mouse embryonic hearts from 11 dpc through 13 dpc, which is prior to the establishment of the coronary circulation. The authors found two types of blood islands: one formed by migrating nucleated erythroblasts and endothelial cells and the second one by emergence of erythroblast-like and endothelial-cell progenitors.…”
Section: Vasculaturementioning
confidence: 97%